Modelling of BST thin film varactors for wireless communication systems / Muhammad Farid Abdul Khalid and Kay Latham - Abdul Khalid, Muhammad Farid; Latham, Kay (UiTM Press, 2025)
Barium Strontium Titanate (BST) is a versatile material with numerous applications in today’s modern technology primarily due to its ferroeletric and dielectric properties. BST thin film varactos are increasingly recognized for their potential in wireless comuunication applications due to its unique properties, tunability and power handling capability. This paper presents the modelling of a BST thin film varactor on sapphire substrate and, the correlation between its tunability and 1 dB compression point. A parametric analysis was performed to investigate the impact of varying its interdigital capacitor (IDC) geometry on the shape of the nonlinear capacitance-voltage (C-V) curve. Three distinct C-V curves namely narrow, broad and intermediate varactors were determined and their tunabilities and 1 dB compression points were derived. Comparisons were made between the simulated and measured results where the narrow varactor achieved the highest tunability of ~50 % and the broad varactor achieved the highest 1 dB compression point of ~41 dBm. The results demonstrate the potential for these varactors to be incorporated in wireless communication systems.